DEVELOPMENT OF THE TECHNIQUE OF QUANTITATIVE DEFINITION OF TRIAZAVIRIN IN WATER SOLUTIONS WITH USE OF THE SPECTROPHOTOMETRY METHOD - M. Yu. Kinev; O. A. Melnikova; A. Yu. Petro; D. V. Zaboyarkina (Бюллетень сибирской медицины)
Authors of article developed techniques of quantitative definition Triazavirin in water solutions with use of a method of a spectrophotometry. Three options of a method of a s spectrophotometry are used: direct spectrophotometry, spectrophotometry according to A.M. Firordt, a spectrophotometry with use of standard solution. For all techniques calculation of metrological characteristics is carried out. The developed techniques of quantitative definition were applicable for practical use in the pharmaceutical analysis. The relative error of quantitative definition Triazavirin in water solutions made 0.37%, 0.14% and 8.29% respectively for a direct spectrophotometry, a spectrophotometry with use of standard solution, a spectrophotometry according to A.M. Firordt.